Interlaminar endoscopic lateral recess decompression—surgical technique and early clinical results - Birjandian, Zeinab; Emerson, Samuel; Telfeian, Albert E.; Hofstetter, Christoph P. (Journal of Spine Surgery; Vol 3, No 2 (June 30, 2017): Journal of Spine Surgery, 2017)
Background: Lateral recess stenosis is a common pathology causing de-novo or residual radicular pain following lumbar spine surgery. Diagnostic criteria and treatment strategies for symptomatic lateral recess stenosis are not well established. Methods: We identified ten patients in our prospective patient database (n=146) who underwent endoscopic interlaminar decompression for unilateral symptomatic lateral recess stenosis. Lateral recess height and angle were measured on axial T2-weighted MRI. Values from the symptomatic side were compared to the contralateral side which served as asymptomatic control. Oswestry Disability Index (ODI) and Visual Analogue Scale (VAS) for back and leg pain were collected preoperatively, postoperatively and at last follow-up. Results: Preoperative MRI revealed that both lateral recess angle and height were significantly smaller on the symptomatic compared to the asymptomatic side (angle: 19.3˚ vs. 35.7˚; height: 2.9 vs. 5.7 mm; P